Vulnerability to low-dose combination of irinotecan and niraparib in ATM-mutated colorectal cancer - Pietro Paolo Vitiello; Giulia Martini; Luigi Mele; Emilio Francesco Giunta; Vincenzo De Falco; Davide Ciardiello; Valentina Belli; Claudia Cardone; Nunzia Matrone; Luca Poliero; Virginia Tirino; Stefania Napolitano; et al. (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract Background Despite the advancements in new therapies for colorectal cancer (CRC), chemotherapy still constitutes the mainstay of the medical treatment. For this reason, new strategies to increase the efficacy of chemotherapy are desirable. Poly-ADP-Ribose Polymerase inhibitors (PARPi) have shown to increase the activity of DNA damaging chemotherapeutics used in the treatment of CRC, however previous clinical trials failed to validate these results and pointed out dose-limiting toxicities that hamper the use of such combinations in unselected CRC patients. Nevertheless, in these studies little attention was paid to the mutational status of homologous recombination repair (HRR) genes. Methods We tested the combination of the PARPi niraparib with either 5-fluorouracil, oxaliplatin or irinotecan (SN38) in a panel of 12 molecularly annotated CRC cell lines, encompassing the 4 consensus molecular subtypes (CMSs). Synergism was calculated using the Chou-Talalay method for drug interaction. A correlation between synergism and genetic alterations in genes involved in homologous recombination (HR) repair was performed. We used clonogenic assays, mice xenograft models and patient-derived 3D spheroids to validate the results. The induction of DNA damage was studied by immunofluorescence. Results We showed that human CRC cell lines, as well as patient-derived 3D spheroids, harboring pathogenic ATM mutations are significantly vulnerable to PARPi/chemotherapy combination at low doses, regardless of consensus molecular subtypes (CMS) and microsatellite status. The strongest synergism was shown for the combination of niraparib with irinotecan, and the presence of ATM mutations was associated to a delay in the resolution of double strand breaks (DSBs) through HRR and DNA damage persistence. Conclusions This work demonstrates that a numerically relevant subset of CRCs carrying heterozygous ATM mutations may benefit from the combination treatment with low doses of niraparib and irinotecan, suggesting a new potential approach in the treatment of ATM-mutated CRC, that deserves to be prospectively validated in clinical trials.